Can MOOC help to prepare a well-trained specialist for aerospace industry?; MATEC Web of Conferences; Vol. 158 : Space Engineering - Ivanova V. S. Veronika Sergeevna; Mertins K. V. Kseniya Viktorovna; Barabanova Yu. A. Julia Aleksandrovna; Yurkina I. Irina (2018, 2018)
Title screen